ChemInform Abstract: Sodium‐Hydroxide‐Mediated Synthesis of Highly Functionalized [1, 6]‐Naphthyridines in a One‐Pot Pseudo Five‐Component Reaction. Issue 11 (18th March 2014) - Sarkar, Satavisha; Das, Deb K.; Khan, Abu T.
Abstract The title reaction proceeds under mild conditions with high chemoselectivity and uses easily available materials.